Does Internal Locus of Control Get You Out of Homelessness? - Santiago Budría; Alejandro Betancourt-Odio; Eszter Wirth (Institute of Labor Economics (IZA), 2023)
This paper examines the role of internal locus of control in shaping transitions into homelessness. The data is taken from a longitudinal Australian dataset drawn from a sample of vulnerable individuals. The results, based on a Wooldridge Conditional Maximum Likelihood (WCML) estimator, show that individuals high in internal locus of control are significantly less likely to enter a homeless episode.
Keywords: D31; I32; C23; 330; locus of control; homelessness; dynamic probit model